2016
DOI: 10.1111/andr.12250
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of apolipoprotein D in male reproductive system of rats by high‐fat diet

Abstract: Apolipoprotein D, a 29-kDa secreted glycoprotein that belongs to the lipocalin superfamily, is widely expressed in various tissues and associated with lipid metabolism as a component of high-density lipoproteins. Although Apolipoprotein D binds to small hydrophobic ligands including cholesterol, little is known about effects of high-fat diet with cholesterol on expression of Apolipoprotein D in the male reproductive tract. Therefore, we investigated Apod expression in penises, prostate glands, and testes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…In the past few years, a number of miRNA have been found to alter experimentally the expression of some Lipocalins. miRNAs 299-3p, 423-3p and 490-3p were associated to ApoD expression in rat [51]; miRNAs 18b-5p, 19b-3p, 99a-5p, 100-5p, 145-5p, 214-3p and 138 alter Lcn2 expression [52,53], and miRNA 573 affects ApoM expression [54]. Some of these miRNAs were detected by the PITA algorithm [23], but they were below the ΔΔG threshold of -10 Kcal/mol to be considered accessible.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, a number of miRNA have been found to alter experimentally the expression of some Lipocalins. miRNAs 299-3p, 423-3p and 490-3p were associated to ApoD expression in rat [51]; miRNAs 18b-5p, 19b-3p, 99a-5p, 100-5p, 145-5p, 214-3p and 138 alter Lcn2 expression [52,53], and miRNA 573 affects ApoM expression [54]. Some of these miRNAs were detected by the PITA algorithm [23], but they were below the ΔΔG threshold of -10 Kcal/mol to be considered accessible.…”
Section: Resultsmentioning
confidence: 99%
“…The production of immature sperm is one of the main causes of male infertility. In a previous study, we identified changes in the expression of apolipoprotein D, a cholesterol-binding lipoprotein in male reproductive organs of rats fed a highcholesterol diet (Lim et al, 2016). However, no studies, to the best of our knowledge, have identified the expression of genes involved in sperm maturation and fertilization in the testes of mammals fed cholesterol.…”
Section: Discussionmentioning
confidence: 98%
“…The authors also reported that miR-423-3p targeted genes involved in fatty acid metabolism and biosynthesis pathways. The role of this miRNA in regulating lipid metabolism was shown in rats fed with a high-fat diet that resulted in increased expression of miR-423-3p and correlated inversely with the expression of apolipoprotein D [ 34 ]. Thus, this miRNA seems a regulator of fat tissue metabolism during allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%